2022
DOI: 10.3390/su142113957
|View full text |Cite
|
Sign up to set email alerts
|

A New Method to Improve the Environmental Sustainability of the Operating Room: Healthcare Sustainability Mode and Effect Analysis (HSMEA)

Abstract: The purpose of this study was to describe a new method to effectively improve the environmental impact of operating rooms through a systematic approach. A proven successful prospective risk analysis tool to improve the safety of complex healthcare processes (Healthcare Failure Mode and Effect Analysis) was adapted to reduce the environmental impact of surgical waste. For this novel method, named the Healthcare Sustainability Mode and Effect Analysis (HSMEA), a multidisciplinary team, using a structured step-by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 34 publications
0
13
2
Order By: Relevance
“…De Ridder et al 38 found that cotton gauzes and disposable surgical gowns were a carbon footprint hotspot for caesarean section at a university hospital. Blue wraps, used to pack surgical instruments, represented the greatest environmental burden in the preparation room.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…De Ridder et al 38 found that cotton gauzes and disposable surgical gowns were a carbon footprint hotspot for caesarean section at a university hospital. Blue wraps, used to pack surgical instruments, represented the greatest environmental burden in the preparation room.…”
Section: Resultsmentioning
confidence: 99%
“…The included articles were published from 2004 onwards, with the majority of studies published in recent years (2020 to 2022; Table 1). The environmental impact regarding the following services, procedures or products within the specialty of obstetrics and gynaecology was reported (Figure 1): mode of delivery (n = 3, 17.6%), [36][37][38] hysterectomy (n = 3, 17.6%), [39][40][41] staging procedure for endometrial cancer (n = 1, 5.8%), 42 vaginal specula (n = 1, 5.8%), 43 menstrual products (n = 6, 35.2%), [44][45][46][47][48][49] gynaecological oncology consultation (n = 1, 5.8%) 50 and general principles relevant to obstetric and gynaecological surgery (n = 2, 11.7%). 51,52…”
Section: Study Selection and Topicsmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Ideally, all plastic disposables should be made from either bioplastics or recycled plastic (and go on to be recycled), and instrument packs should be evaluated to ensure that only essential instruments are included. Notably, Ridder et al 10 reduced their carbon footprint of caesarean birth by 2.5 kgCO 2 e by adjusting the contents of the surgical pack.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Environmental variables affect the degree of satisfaction of patients and employees [10][11][12]. (3) Key departments include ICU, emergency [13], and operation rooms [14]. But, there are few pieces of research on community public hospitals.…”
Section: Introductionmentioning
confidence: 99%